Radio-pathological Findings of Male Breast Lesions in the sub-Saharan African Population - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Globally, information about male breast lesions is scarce. Focus is often on clinical presentation with less emphasis on radiological characteristics.Aim:To document and highlight the imaging and pathology findings of male breast diseases in a Sub-Saharan Africa.Materials and Methods:Male patients who had breast ultrasound and/or mammography in a tertiary hospital over a 10year period were reviewed retrospectively. Biodata of the patients, symptoms, and imaging findings with pathology reports were documented and analyzed. Breast ImagingReporting and Data Systems lexicon was used.Results:Fiftyfive male patients were seen and constituted about 1.82% of the total number of breast cases. Their age range was 12–85 years, with a mean of 35.89 ± 18.45 years. Four of these patients had mammograms only, 49 had breast ultrasound scan alone, whereas 2 had a combination of both modalities. The most common clinical indication and radiological findings were breast swelling (60%) and gynecomastia (72.7%), respectively. Gynecomastia was the most common finding pathologically (67.6%), whereas malignancy constituted 14.7%. The lesions were observed more in the right breast (40.7%).Conclusions:Imaging plays a significant role in the evaluation of male breast diseases. Ultrasound has high accuracy in the detection of benign lesions. This study found gynecomastia as the most common benign male breast disease. Breast cancer, although rare cancer among males was observed in a 35yearold young male.